Low rate of new‐onset primary biliary cholangitis in a cohort of anti‐mitochondrial antibody‐positive subjects over six years of follow‐up. (4th December 2019) - Zandanell, S.; Strasser, M.; Feldman, A.; Tevini, J.; Strebinger, G.; Niederseer, D.; Pohla‐Gubo, G.; Huber‐Schönauer, U.; Ruhaltinger, S.; Paulweber, B.; Datz, C.; Felder, T.K.; et al.
Abstract: Background and Aims: Anti‐mitochondrial antibodies (AMA) are closely linked to primary biliary cholangitis (PBC). The prevalence of AMA in the general population is low, and AMA positivity may precede PBC. We aimed to determine the natural history of subjects with positive AMA. Methods: In total, 302 patients were tested AMA‐positive over a ten‐year period. Of these, immunoblotting confirmed specific AMA in 184 (29 male, 155 female, age 59.6 ± 14.1 years). These subjects were invited to our liver outpatient clinic for clinical and biochemical re‐evaluation. Detailed clinical history data were additionally collected from the hospital computer system and by telephone. The subsequent course with regard to mortality, liver‐related morbidity, extrahepatic co‐morbidities and effectiveness of PBC treatment was determined in 150 subjects (81.5%). Results: After 5.8 ± 5.6 years of follow‐up (FU), of 184 AMA‐positive subjects, 28 subjects (15.2%; liver‐related mortality n = 5) were deceased, and 122 subjects (66.3%) completed FU while 34 subjects (18.5%) were not available for FU. The 122 patients who completed FU were 63 patients with established PBC, six de novo cases of PBC (10.2% of 59 initially at risk), 42 (34.4%) subjects were still AMA‐positive without PBC, and 11 (9.0%) subjects were AMA‐negative at FU. Conclusions: Anti‐mitochondrial antibodies‐positive patients without PBC at baseline infrequently developed PBC over six years of FU. AMA positivity represented a transient serological autoimmune phenomenon in a significant proportion of subjects. Abstract :